Harmony in Diversity: Exploring Religious Moderation Perspectives through Interfaith Dialogue - Moh. Muslih; Dewi Anggraeni; Mochamad Iqbal Abdul Ghonii (JURNAL PENELITIAN, 2023)
Religious moderation becomes a catalyst for building a harmonious life in Indonesia. This research explores religious moderation from the perspective of religions in Indonesia, both theoretically and practically. This research uses a qualitative and comparative study approach to see the esoteric values in each religion related to religious moderation. Data collection techniques include interviews, focus group discussions, and documentation studies. The analysis focused on verifying data from religious figures and religious texts. The results of the study revealed that 1) religious moderation becomes urgent to internalize religious teachings substantively and to address the problem of violence in the name of religion, 2) religious moderation is in line with the universal values of all religions, 3) the term moderation or middle way is found in the scriptures of each religion, 4) interfaith dialogue as an effort to open up openness between religions and realize cross-religious cooperation.